Combined CT- and fluoroscopy-guided nephrostomy in patients with non-obstructive uropathy due to urine leaks in cases of failed ultrasound-guided procedures - Sommer, Christof-Matthias; Huber, J.; Radeleff, Boris; Hosch, Waldemar P.; Stampfl, Ulrike; Lönard, Brigitta Michaela; Hallscheidt, Peter; Haferkamp, A.; Kauczor, Hans-Ulrich; Richter, Götz Martin (European journal of radiology, 2011)
Aim - To report our experience of combined CT- and fluoroscopy-guided nephrostomy in patients with non-obstructive uropathy due to urine leaks in cases of failed ultrasound-guided procedures. - Patients and methods - Eighteen patients (23 kidneys) with non-obstructive uropathy due to urine leaks underwent combined CT- and fluoroscopy-guided nephrostomy. All procedures were indicated as second-line interventions after failed ultrasound-guided nephrostomy. Thirteen males and five females with an age of 62.3±8.7 (40-84) years were treated. Urine leaks developed in majority after open surgery, e.g. postoperative insufficiency of ureteroneocystostomy (5 kidneys). The main reasons for failed ultrasound-guided nephrostomy included anatomic obstacles in the puncture tract (7 kidneys), and inability to identify pelvic structures (7 kidneys). CT-guided guidewire placement into the collecting system was followed by fluoroscopy-guided nephrostomy tube positioning. Procedural success rate, major and minor complication rates, CT-views and needle passes, duration of the procedure and radiation dose were analyzed. - Results - Procedural success was 91%. Major and minor complication rates were 9% (one septic shock and one perirenal abscess) and 9% (one perirenal haematoma and one urinoma), respectively. 30-day mortality rate was 6%. Number of CT-views and needle passes were 9.3±6.1 and 3.6±2.6, respectively. Duration of the complete procedure was 87±32min. Dose-length product and dose-area product were 1.8±1.4Gycm and 3.9±4.3Gycm2, respectively. - Conclusions - Combined CT- and fluoroscopy-guided nephrostomy in patients with non-obstructive uropathy due to urine leaks in cases of failed ultrasound-guided procedures was feasible with high technical success and a tolerable complication rate.
Online verfügbar 23 October 2010
Gesehen am 18.10.2022